PENGARUH TEKNIK EFFLEURAGE TERHADAP INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF PADA IBU BERSALIN DI BPS Hj. MUTHOLI’AH, SST - Purwati, Heni (JURNAL KEPERAWATAN BINA SEHAT, 2013)
The pain of childbirth was experienced by most women, this pain is unique and different for every individual. Non-pharmacological pain control becomes cheaper, simpler, effective and without adverse effects, one of which is the technique eflleurage. Effleurage of the abdomen is one of the non-pharmacological methods which are usually used in the Lamaze method to reduce pain in normal labor. This research aimed to determine the effect of effleurage technique on active phase of the first stage of labor pain intensity on maternal in private midwife Hj. Mutholiah Wonodadi Village Kutorejo District Mojokerto Regency. Research design was pre experimental type one group pre test post test design. Its population were all women giving birth in BPS Hj. Mutholiah, SST Village Wonodadi Kutorejo Mojokerto district, amount 17 people. The sampling technique used consecutive sampling to obtain 15 samples. Data analysis used was Wilcoxon test with ρ value <0.05. It means that there was effect of effleurage technique on active phase of the first stage of labor pain intensity on maternal in private midwife Hj. Mutholiah Wonodadi Village Kutorejo District Mojokerto Regency. Gently caress the abdomen resulting in pain that is transmitted will be inhibited, this resulted in the cerebral cortex does not receive the response message so that the pain decreased pain.Keywords: active phase pain intensity,effleurage technique